JUAL BELI MINUMAN BERALKOHOL PADA KARAOKE KELUARGA DI KOTA PEKANBARU - Intan Rahmadona; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Family karaoke business is growing rapidly in various parts of Indonesia, especially in urban areas, including in Pekanbaru City. To seek profit, business actors vying to find a business gap that guarantees entertainment business is one form of business that many run by business actors and is in great demand by the community. In terms of profit, the family karaoke business is not only running a business just for singing, but business actors provide various foods and beverages that are registered in every family karaoke room. Consumers not only sing in the room but can order food or drink that is registered in the family karaoke. Business actors also sell a variety of beverages containing alcohol written in the drink menu. This is contrary to the provisions of Article 1 Point 17 of Pekanbaru City Regulation Number 5 Year 2011 on Entertainment Tax means that family karaoke is a place of entertainment that does not sell alcoholic beverages.This type of research can be classified in the type of sociological legal research, because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem under study. The research was conducted in Pekanbaru City Office of Industry and Trade, Family Box Karaoke, Happy Puppy Karaoke and Koro-Koro Karaoke, while the population and sample were all parties related to the problem studied, data source used, primary data, secondary data and Tertiary data, data collection techniques in this study with interviews and literature study.From the results of research and discussion can be concluded that, First, the consequences of legal buying and selling alcoholic beverages on karaoke family Pekanbaru namely the existence of a legal bond between the seller and buyer in the sale and purchase of alcoholic beverages in the family karaoke. Second, the responsibility of business actors to the sale and purchase of alcoholic beverages is the business actors prioritize supervision on the sale of alcoholic beverages in every family karaoke.Keywords: Family Karaoke - Consumer Protection - Department of Industry and Trade Pekanbaru City